Urbanization in China and the role of social and natural capital in land acquisition and transfer arrangements - Feng, Haying; Squires, Victor R. (Advances in Social Sciences Research Journal, 2022)
The paper is in several parts. We explain the context of the study area that is characterized by land acquisition and transfer (LAT) by local government (often against the wishes of the local villagers). We report on a methodology that is simple, yet robust, that enables local land users and other interested parties to quantify the social capital of local people in rural and peri-urban areas of Guangxi Zhuang Autonomous Region (GZAR) and assess the extent to which social capital influences the bargaining power of land users when faced with acquisition of their cropland, grazing land, woodlands, water and other environmental goods and services. Finally, we explore the notion that social capital can be a force to create a more even playing field and influence the outcomes of land grab for industrial, infrastructure and urban development. Interest in the concept of social capital and its application has increased rapidly over the past few years with the realization that social bonds and norms are important for achieving sustainability. Ferdinand Tönnies identified the value of the ideas surrounding social capital as early as 1887, but later scholars gave it a theoretical framework. Social capital implies that there are aspects of social structure and organization that act as resources for individuals, allowing them to realize their personal aims and interests. Often, social capital is defined as trust, norms of reciprocity, and networks among individuals that can be drawn upon for individual or collective benefit. Social capital is different between urbanites and rural dwellers, especially farmers. In this paper, we focus on how social capital serves the interests of individuals or collectives. Social capital based on kinship and geopolitical position plays an important role in affecting rural land transfer. Rural land transfer (also called LAT) is becoming a highly contested matter as China moves to implement its plan to increase the proportion of urban dwellers to 70% by 2030(Ma et al., 2018). Natural capital (a sub-set of social capital) should always be maintained as it is critical to sustainable economic development representing, as it does, a multidimensional concept that mirrors the different frameworks of various scientific disciplines and social groups used in valuing nature. Widespread and rampant LAT that accompanies accelerated economic development in peri-urban and rural areas (Ma et al., 2018) needs to take critical natural capital into account.